Neodymium(III) PVC Membrane Electrodchemical Sensor Based on N-benzoylethylidene-2-aminobenzylamine - Hassan Ali Zamani; Mojdeh Zaferoni; Soraia Meghdadi (E-Journal of Chemistry)
The N-benzoylethylidene-2-aminobenzylamine (BEA) was used as a suitable ionophore in construction of neodymium ion selective electrode. The electrode with composition of 30% PVC, 58% solvent mediator (NB), 2% ionophore (BEA) and 10% anionic additive (OA) shows the best potentiometric response characteristics. The Nd3+ sensor exhibits a Nernstian slope of 21.2 ± 0.2 mV decade-1 over the concentration range of 1.0 × 10-6 to 1.0 × 10-2 mol L-1, and a detection limit of 6.3 × 10-7 mol L-1 of Nd3+ ions. The potentiometric response of the sensor is independent of the solution pH in the range of 2.4–8.5. It has a very short response time, in the whole concentration range (~7 s), and can be used for at least eight weeks. The proposed sensor revealed high selectivity with respect to all common alkali, alkaline earth, transition and heavy metal ions, including members of the lanthanide family other than Nd3+. The Nd3+ sensor was successfully applied as an indicator electrode in the potentiometric titration of Nd3+ ions with EDTA. The electrode was also employed for the determination of the fluoride ion in two mouth wash preparations.